1993
DOI: 10.2307/3586950
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Speech Acts by EFL Learners

Abstract: Descriptions are now available of the speech act realizations of native speakers in given situations and of expected deviations from these patterns in the speech of nonnative speakers. Still largely lacking is a description of the processes involved in the production of these speech act utterances. This paper reports a study describing ways in which nonnative speakers assess, plan, and execute such utterances. The subjects, 15 advanced English foreign language learners, were given six speech act situations (tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
117
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(120 citation statements)
references
References 18 publications
2
117
0
1
Order By: Relevance
“…Another important point is that, on the whole, the metacognitive strategy of monitoring was considerably more focused on language-related issues (i.e., grammar, vocabulary, pronunciation) than the messages conveyed when a particular student was speaking, but the reverse was the case when he or she was listening to a partner. What is also striking is the evident lack of focus on pragmatic considerations, which figured prominently in the research project undertaken by Cohen and Olshtain (1993) referred to above, a situation that can perhaps in part be attributed to different types of tasks used in both studies (i.e., role-plays designed to elicit concrete speech acts vs. more general communication tasks). Finally, particularly disconcerting is the fact that the participants often left blank spaces, in most cases provided rather general responses failing to give details of SSs use, or offered answers that were entirely irrelevant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important point is that, on the whole, the metacognitive strategy of monitoring was considerably more focused on language-related issues (i.e., grammar, vocabulary, pronunciation) than the messages conveyed when a particular student was speaking, but the reverse was the case when he or she was listening to a partner. What is also striking is the evident lack of focus on pragmatic considerations, which figured prominently in the research project undertaken by Cohen and Olshtain (1993) referred to above, a situation that can perhaps in part be attributed to different types of tasks used in both studies (i.e., role-plays designed to elicit concrete speech acts vs. more general communication tasks). Finally, particularly disconcerting is the fact that the participants often left blank spaces, in most cases provided rather general responses failing to give details of SSs use, or offered answers that were entirely irrelevant.…”
Section: Discussionmentioning
confidence: 99%
“…Interviews conducted with 10 high-and 9 low-achievers revealed that the former were more likely to engage in functional practice, as exemplified by such strategies as actually using the TL for communication, thinking in that language, talking to oneself, or reading in order to obtain the models for speaking. In another study, whose focus, however, was primarily on pragmatics, Cohen and Olshtain (1993) examined the performance of the speech acts of apologies, complains and requests in role-play activities by 15 advanced learners of English as a foreign language. The analysis of the data obtained by means of think-aloud protocols resulted in the identification of four major strategies (i.e., planning, thinking in two or three languages, searching for TL forms in various ways, and paying scant attention to grammar and pronunciation), allowing categorization of the participants into metacognizers, avoiders and pragmatists.…”
Section: Overview Of Previous Research On Speaking Strategiesmentioning
confidence: 99%
“…Cross-cultural studies of speech acts have shown that L2 learners face problems in using speech acts when they communicate with native speakers of the target language (Blum-Kulka and Olshtain 1984;Kasper 1990;Beebe et. al 1990;Koike 1989;Cohen and Olshtain 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, as Babaie and Shahrokhi (2015) report, numerous studies have indicated that the conventions of politeness are different from one culture to another culture (e.g., see Matsumura, 2001;Golato, 2002;Nelson et al, 1996;Blum-Kulka, House, & Kasper, 1989;Cohen & Olshtain, 1993;DeCapua, 1998;Boxer, 1993;Einsenstein & Bodman, 1993;Beebe & Takahashi, 1989;Fe´lix-Brasdefer, 2004;Gass & Houck, 1999;Kwon, 2004).…”
Section: Research Concernmentioning
confidence: 99%